Aggregation of protein therapeutics enhances their immunogenicity: causes and mitigation strategies. Issue 4 (10th May 2021) - Lundahl, Mimmi L. E.; Fogli, Silvia; Colavita, Paula E.; Scanlan, Eoin M.
Abstract : Protein aggregation of biotherapeutics increases their immunogenicity, leading to immune-mediated adverse effects. In this review we discuss immune activation pathways, causes of aggregation and mitigation strategies. Abstract : Protein aggregation in biotherapeutics has been identified to increase immunogenicity, leading to immune-mediated adverse effects, such as severe allergic responses including anaphylaxis. The induction of anti-drug antibodies (ADAs) moreover enhances drug clearance rates, and can directly block therapeutic function. In this review, identified immune activation mechanisms triggered by protein aggregates are discussed, as well as physicochemical properties of aggregates, such as size and shape, which contribute to immunogenicity. Furthermore, factors which contribute to protein stability and aggregation are considered. Lastly, with these factors in mind, we encourage an innovative and multidisciplinary approach with regard to further research in the field, with the overall aim to avoid immunogenic aggregation in future drug development.